Sexual Harassment During a Pandemic and The Legal Consequences It Causes (Universitas Negeri Semarang, 2020)
Sexual harassment is unwanted and unwanted behavior or attention of a sexual nature and results in disturbing the harasser. Sexual harassment includes, but is not limited to: sexual payments for wanting something, coercion of sexual activity, derogatory statements about sexual orientation or sexuality, requests for sexual favors by the perpetrator, speech or behavior that has a sexual connotation; all can be classified as sexual harassment. This action can be conveyed directly or implicitly. The effect is on the victim, who is considered to be causing problems and not the perpetrator. In general, victims will keep their mouths shut, sometimes for a very long time, for these reasons, and there is a fear that they will become targets of abuse. They don't talk about it with friends or family. The healing process will be more difficult when there is denial from the institution, distrust, or blaming the victim. The rampant sexual harassment that is happening in Indonesia is troubling most people. Even during the current covid-19 pandemic, there is an increase in sexual harassment that occurs against women, even worse, it also happens to children who are still underage. Komnas Perempuan identified that during 2001 to 2012, there were at least 35 women who were victims of sexual violence every day. Meanwhile, the data released by Komnas Perempuan during the current covid-19 pandemic is 1,902 cases of sexual harassment that have occurred in Indonesia, as of Saturday, July 3, 2021. In this case, it is clear that there is still a lack of legal protection for cases involving threaten a person's personal personality, especially in cases of sexual harassment to sexual violence.